Program Pendidikan Masyarakat Dan Kebijakan Pembangunan Sosial Ekonomi Menuju Sistem Peternakan Masa Depan - Wahidin Wahidin (Jurnal Ilmiah Kanderang Tingang, 2021)
Indonesian economy is predicted to keep growing in the future and it will encourage consumption of livestock products. On the hand, supply of domestic livestock products such as meat and milk is relatively low that the government allows meat and milk imports. Livestock production sector has to anticipate this issue to support food security and to lessen usage of foreign exchange. Current domestic livestock sector is difficult to anticipate the current issue and it needs to restructure livestock industry toward the expected system. Livestock development orientation and effectiveness of the programs are undecided. We need to design the expected livestock structure in the future and types of the action to take to realize it. This paper illustrates those aforementioned ideas through analysis review and livestock research synthesis.